Neutralizing antibodies for SARS-CoV-2 in stray animals from Rio de Janeiro, Brazil. - Helver Gonçalves Dias; Maria Eduarda Barreto Resck; Gabriela Cardoso Caldas; Alessandro Fioretti Resck; Natália Valente da Silva; Aline Marcele Vieira Dos Santos; Thiago das Chagas Sousa; Maria Halina Ogrzewalska; Marilda Mendonça Siqueira; Alex Pauvolid-Corrêa; Flavia Barreto Dos Santos (PLoS ONE)
The epidemic of coronavirus disease 2019 (COVID-19), caused by a novel Betacoronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) became a public health emergency worldwide. Few reports indicate that owned pets from households with at least one human resident that was diagnosed with COVID-19 can be infected by SARS-CoV-2. However, the exposure to SARS-CoV-2 of pets from households with no COVID-19 cases or stray animals remains less assessed. Using real-time reverse transcriptase polymerase chain reaction (RT-PCR) and plaque reduction neutralization test (PRNT90), we investigated the infection and previous exposure of dogs and cats to SARS-CoV-2 during the ongoing COVID-19 epidemic in Rio de Janeiro, Brazil. From June to August 2020, 96 animals were sampled, including 49 cats (40 owned and 9 stray) and 47 dogs (42 owned and 5 stray). Regarding owned pets, 75.6% (62/82) belonged to households with no COVID-19 cases. Samples included serum, and rectal and oropharyngeal swabs. All swabs were negative for SARS-CoV-2 RNA, but serum samples of a stray cat and a stray dog presented neutralizing antibodies for SARS-CoV-2, with PRNT90 titer of 80 and 40, respectively. Serological data presented here suggest that not only owned pets from households with COVID19 cases, but also stray animals are being exposed to SARS-CoV-2 during the COVID-19 pandemic.